Outcomes in a multi-institutional cohort of patients treated with intraoperative radiation therapy for advanced or recurrent renal cell carcinoma - Paly, Jonathan Judd; Hallemeier, Christopher L.; Biggs, Peter J.; Niemierko, Andrzej; Röder, Falk; Martínez-Monge, Rafael; Whitson, Jared; Calvo, Felipe A.; Fastner, Gerd; Sedlmayer, Felix; Wong, William W.; Ellis, Rodney J.; et al. (International journal of radiation oncology, biology, physics, 2014)
Purpose/Objective(s) - This study aimed to analyze outcomes in a multi-institutional cohort of patients with advanced or recurrent renal cell carcinoma (RCC) who were treated with intraoperative radiation therapy (IORT). - Methods and Materials - Between 1985 and 2010, 98 patients received IORT for advanced or locally recurrent RCC at 9 institutions. The median follow-up time for surviving patients was 3.5 years. Overall survival (OS), disease-specific survival (DSS), and disease-free survival (DFS) were estimated with the Kaplan-Meier method. Chained imputation accounted for missing data, and multivariate Cox hazards regression tested significance. - Results - IORT was delivered during nephrectomy for advanced disease (28%) or during resection of locally recurrent RCC in the renal fossa (72%). Sixty-nine percent of the patients were male, and the median age was 58 years. At the time of primary resection, the T stages were as follows: 17% T1, 12% T2, 55% T3, and 16% T4. Eighty-seven percent of the patients had a visibly complete resection of tumor. Preoperative or postoperative external beam radiation therapy was administered to 27% and 35% of patients, respectively. The 5-year OS was 37% for advanced disease and 55% for locally recurrent disease. The respective 5-year DSS was 41% and 60%. The respective 5-year DFS was 39% and 52%. Initial nodal involvement (hazard ratio [HR] 2.9-3.6, P<.01), presence of sarcomatoid features (HR 3.7-6.9, P<.05), and higher IORT dose (HR 1.3, P<.001) were statistically significantly associated with decreased survival. Adjuvant systemic therapy was associated with decreased DSS (HR 2.4, P=.03). For locally recurrent tumors, positive margin status (HR 2.6, P=.01) was associated with decreased OS. - Conclusions - We report the largest known cohort of patients with RCC managed by IORT and have identified several factors associated with survival. The outcomes for patients receiving IORT in the setting of local recurrence compare favorably to similar cohorts treated by local resection alone suggesting the potential for improved DFS with IORT.